Comparison of Pain-Related and Psychological Variables between Acute and Chronic Migraine Patients, and Factors Affecting Headache Chronicity - Farhad Emadi; Farkhondeh Sharif; Maryam Shaygan; Maryam Shaygan; Nasrin Sharifi; Nahid Ashjazadeh (Shiraz University of Medical Sciences, 2019)
Background: Migraine headache is classified as acute or chronic. In recent years, efforts have been made to identify the factors that might predispose individuals to develop the chronic-type headache. The present study aimed to draw a comparison between patients with acute and chronic migraine in terms of demographic, pain-related, and psychological variables. In addition, we also investigated factors affecting headache chronicity in such patients. Methods: The present cross-sectional study was conducted during 2017-2018. The target sample consisted of 250 patients with acute or chronic migraine who referred to various clinics affiliated to Shiraz University of Medical Sciences (SUMS), Shiraz, Iran, recruited by convenience sampling. All the participants filled in the questionnaires related to demographic characteristics, pain intensity, disability, depression, emotional intelligence, and anger. The data were analyzed using SPSS software (version 22.0) with t test, Chi-square test, and logistic regression analysis. Pstatistically significant. Results: Patients suffering from chronic migraine experienced higher levels of disability, depression, anger, and had lower levels of emotional intelligence compared to those with acute migraine. Based on the logistic regression analysis, variables that had a significant effect on headache chronicity were female gender (OR=5.81), married status (OR=3.77), patients with lower level of education (OR=0.26), headache duration (OR=1.53), disability (OR=0.28), depression (OR=3.66), and anger (OR=5.04). Conclusion: Variables such as disability, depression, and lack of anger control were among the key factors associated with headache chronicity in migraine patients.